PERAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) DALAM MENCIPTAKAN MEANINGFUL LEARNING DI SEKOLAH DASAR - Fia Afiatul Maula; Bagas Mukti Nasrowi (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the concept of Technological Pedagogical Content Knowledge (TPACK) in the teaching and learning process at the elementary school level and to explore its contribution to the development of meaningful learning. The research adopts a qualitative approach through a library research method. The data utilized in this study consist of secondary sources derived from books, national and international scholarly journal articles, previous studies, and official documents related to TPACK and meaningful learning in elementary education. Data collection was carried out through documentation study by identifying and compiling relevant literature from scientific databases, including Google Scholar and Semantic Scholar. The data were analyzed using content analysis techniques involving the stages of data reduction, data categorization, interpretation, and conclusion drawing. To ensure data credibility, source triangulation was employed. The findings reveal that TPACK represents the integration of technological, pedagogical, and content knowledge that facilitates the creation of interactive, contextual, and student-centered learning environments. The application of TPACK contributes to the realization of meaningful learning through the use of digital technology that encourages students’ active engagement, enhances conceptual understanding, and fosters critical thinking abilities. Nevertheless, the implementation of TPACK still faces several obstacles, particularly the limited digital literacy of teachers and inadequate digital learning infrastructure.